Spittlebug Clastoptera achatina (Hemiptera: Clastopteridae) on pecan trees: Population dynamics, distribution and efficacy of insecticides - Burrola-Morales, Jesús Raúl; García-Nevárez, Gerardo; Carnero-Avilés, Leslie (Ecosistemas y Recursos Agropecuarios, 2022)
The spittlebug Clastoptera achatina is a hemiptera that decreases the quality and production of the nut by feeding on the sap and covering the stigmas with its excretions. The objective of this research was to determine the population fluctuation, the distribution in the treetop and the effect of five insecticides on spittlebugs. The results show three population peaks, the most abundant was during the summer in the municipality of La Cruz with 56% of infested shoots between 2 and 4 m high in the eastern and northern quadrants of the tree. The insecticides sulfoxaflor (3.6 and 7.2 g of a.i. 100 L−1 of water) and chlorpyrifos (72 g of a.i. 100 L−1 of water) presented a control of 100% at 72 and 24 h, respectively, up to 7 days after application. The results contribute to the development of strategies for the control of spittlebugs in pecan. trees.